Soluble Neuropilin-1 in gingival crevicular fluid from periodontitis patients: An exploratory cross-sectional study - Diego Prieto; Gloria Maurer; Maximiliano Sáez; Felipe Cáceres; Karina Pino-Lagos; Alejandra Chaparro (Journal of Oral Biology and Craniofacial Research)
Background: Soluble Neuropilin-1 (sNRP-1) is a glycoprotein with angiogenic and immune regulatory functions, which correspond to processes deeply involved with periodontal diseases. This study’s objective was to determine the concentration of sNRP-1 in gingival crevicular fluid (GCF) samples of severe periodontitis (stages III-IV) compared to mild-moderate (stages I-II) periodontitis patients. Materials and methods: An exploratory cross-sectional study was conducted, including 36 adults subjected to a complete periodontal exam, which recorded the following periodontal parameters: periodontal probing depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), gingival index (GI) and periodontal inflamed surface area (PISA). Periodontitis was defined by two periodontists using the case definition proposed by the 2017 World Workshop for periodontal diseases. GCF samples were collected to determine the levels of sNRP-1 via ELISA. The results were analyzed using descriptive statistics, Mann-Whitney, Kruskal Wallis, and Spearman tests. Results: The levels of sNRP-1 in patient’s GCF with periodontitis in stages III-IV showed a median of 38.385 ​ng/mL (iqr 30.98), in comparison with 20.085 ​ng/mL (iqr 12.74) for stages I-II (p ​= ​0.202). Regardless of the periodontitis stage, we observed a positive correlation between the levels of sNRP-1 in BOP (Rho: 0.45; p ​= ​0.0048), PISA (Rho: 0.50; p ​= ​0.0019), PD (Rho: 0.3; p ​= ​0.015) and GI (Rho: 0.37; p ​= ​0.02). Conclusions: The GCF-sNRP-1 concentration was positively related to periodontal clinical inflammatory parameters and probably could be involved in pro-inflammatory and angiogenic mechanisms observed in periodontitis. Additional studies are necessary to confirm these preliminary results.